Targeted development of informative microsatellite (SSR) markers - Hayden, M. J. (Oxford University Press, 2001)
We describe a novel approach, selectively amplified microsatellite (SAM) analysis, for the targeted development of informative simple sequence repeat (SSR) markers. A modified selectively amplified microsatellite polymorphic loci assay is used to generate multi-locus SSR fingerprints that provide a source of polymorphic DNA markers (SAMs) for use in genetic studies. These polymorphisms capture the repeat length variation associated with SSRs and allow their chromosomal location to be determined prior to the expense of isolating and characterising individual loci. SAMs can then be converted to locus-specific SSR markers with the design and synthesis of a single primer specific to the conserved region flanking the repeat. This approach offers a cost-efficient and rapid method for developing SSR markers for predetermined chromosomal locations and of potential informativeness. The high recovery rate of useful SSR markers makes this strategy a valuable tool for population and genetic mapping studies. The utility of SAM analysis was demonstrated by the development of SSR markers in bread wheat.